Institutional Change and System Support – Reforming the Executive in Norwegian Cities and Regions - Bukve, Oddbjørn; Petter Saxi, Hans (Scandinavian Journal of Public Administration, 2017)
By studying the change from the alderman model to parliamentary rule in Norwegian cities and regions, this article analyses how and why reorganisation of political institutions influ- ences support for the institutions reformed. We adopt a mixed methods approach consisting of a survey of politicians in all seven reformed Norwegian local governments, combined with a case study of reorganised governments with high and low levels of support for par- liamentary rule. We find that support for the institutional model in the reformed local gov- ernments depends on the reform’s effect on different political positions. Politicians in power are more positive towards parliamentary rule than members in opposition are, and politicians from the big parties are more positive compared to representatives from smaller ones. Institutional change affects the interests of these groups in different ways. In turn, the effects that reform has on different interests influence their support for the reformed insti- tutions. System support is also affected by how the change process is implemented. An inclusive political leadership that builds oversized coalitions and allocates positions such as committee chairs to the opposition results in stronger support for parliamentary rule. The overall finding is that both “pure” institutional effects and contextual factors influence sup- port for parliamentary rule. Support increases when there is a high level of readiness and capacity for change. The reform must also include relevant actors in a way meeting de- mands for procedural fairness. The practical implication for reformers is that they must communicate why the organisation needs reform, arrange for sufficient implementation ca- pacity and include relevant participants in decision-making and change processes.